Analysis Of River Ordo In The Tukad Balian Watershed (DAS), Bali Province, Indonesia - Sinaga, Mardame Pangihutan; Simanullang, Ady Frenly; Siburian, Daniel Tony Edyt; Joko Barita Sianipar; Sianipar, Herna Febrianty; Sianturi, Tambos August (UIR PRESS, 2024)
River order research in Tukad Balian Watershed, Bali Province uses ArcGIS Pro to process ASTER GDEM and National DEM data. The analysis is based on: the area and Perimeter of the Watershed, Watershed Length and Width, Land Slope, Average Height, Order and Level of River Branching. The results obtained for the Watershed show that the morphometric value is an area of 15485,20 hectares, a length of 23,08 km, a land slope of 0,40%, and 5 orders of branching rivers with a total of 665 river sections. The shape of Watershed Tukad Balian roundness index value is 7,2. GIS is an effective system for reducing Watershed morphometric information. The research method used is to directly calculate the morphometric parameters of the Tukad Balian Watershed, Bali Province, namely: Area and Perimeter of the Watershed; Watershed Length and weight; River slop or gradient; Average Height; Order and Level of River Branching; Flow Density; and Watershed Form. The conclusion obtained is: The Tukad Balian watershed is a standard-sized watershed with an area of 15.485,20 Ha an average height of 200 meters above sea level and the main river channel is 10,71 Km long. There a plot sections with a total length of 23,08 Km; The elongated shape of the Tukad Balian watershed is in the medium category, where the Tukad Balian Watershed will not experience major flooding.